2008
DOI: 10.1016/s1441-3582(08)70011-9
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Influence of Enjoyment on Customer Loyalty

Abstract: As youth use mobile services for utilitarian and hedonic purposes, their evaluations of mobile service providers may relate to cognitive determinants of service quality, value, and switching costs as well as to affective enjoyment. The findings showed that cognitive determinants related significantly to loyalty, but enjoyment did not. A follow-up investigation suggested that enjoyment moderated relationships between these cognitive determinants and loyalty. Service quality and value related more to loyalty whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 63 publications
(93 reference statements)
3
17
0
4
Order By: Relevance
“…This demand is an increas-ing function of the consumer utility from the product offered by firm i and a declining function of the consumer utility derived from the product offered by the competitor. Such a specification is empirically valid, since consumers derive their demand for a particular good from its utility (cf., e.g., Lee, 1999;Lee & Sung, 2005;Ding, Ross, & Rao, 2010;Gostkowski, 2018), and can easily swap the product offered by a given firm for the product offered by the competitor if the latter product brings sufficiently large utility (cf., e.g., Lee & Murphy, 2008;Wan, Huang, Zhao, Deng, & Fransoo, 2018). Since utility of the product is contingent on price and quality, and the demand for the product depends on utility, the considered firms compete both in price and quality.…”
Section: The Model Of Firm's Product Innovation In Oligopoly With Primentioning
confidence: 99%
“…This demand is an increas-ing function of the consumer utility from the product offered by firm i and a declining function of the consumer utility derived from the product offered by the competitor. Such a specification is empirically valid, since consumers derive their demand for a particular good from its utility (cf., e.g., Lee, 1999;Lee & Sung, 2005;Ding, Ross, & Rao, 2010;Gostkowski, 2018), and can easily swap the product offered by a given firm for the product offered by the competitor if the latter product brings sufficiently large utility (cf., e.g., Lee & Murphy, 2008;Wan, Huang, Zhao, Deng, & Fransoo, 2018). Since utility of the product is contingent on price and quality, and the demand for the product depends on utility, the considered firms compete both in price and quality.…”
Section: The Model Of Firm's Product Innovation In Oligopoly With Primentioning
confidence: 99%
“…Holbrook et al (1984) has pointed out that performance achieved might affect the emotional reaction to playful consumption experience and in turn, emotion state of a person might maintain some circumspections in anticipating successive performance. Perceived enjoyment as one of the emotional determinants is the major contributor to the performance of being loyalty and repatronage behavior (Hart et al, 2007;Lee and Murphy, 2008). Excitement is a combination of pleasure and arousal that can increase approach tendencies, unplanned purchases and hedonic shopping value (Babin and Darden, 1996).…”
Section: Shopping Enjoymentmentioning
confidence: 99%
“…A number of previous studies have confirmed some factors which have an impact on customer loyalty in the field of mobile telecommunication service. For example, service quality (Eshghi, Roy, & Ganguli, 2008;Lee & Murphy, 2008;Ishaq, 2012;M. Hassan, S. Hassan, Nawaz, & Aksel , 2013), corporate image (Kim, Park, & Jeong, 2004;Jallow, 2013;Bayraktar, Tatoglu, Turkyilmaz, & Zaim, 2012;Aydin & Ozer, 2005;Hafeez & Hasnu, 2010;Vranakis, Chatzoglou, & Mpaloukas, 2012), switching barrier (Kim et al, 2004;Liu, Guo & Lee, 2011;Almossawi, 2012;Aydin & Ozer, 2005), perceived value (Bayraktar et al, 2012;Ishaqa, 2012), customer trust (Liu, Guo & Lee, 2011;Ahmad, Husain & Rajput, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%